A theology of spiritual direction for the Presbyterian Church of Southern Africa - Snyman, Kevin (Rhodes University, Faculty of Divinity, Department of Divinity, 1997)
This essay is written in response to a lacuna that appears to exist within the Presbyterian Church of Southern Africa with regard to the ancient and highly regarded ministry of spiritual direction. My primary assertion is that, in the light of what might be perceived of as a crisis of relevance in Presbyterian life and spiritual practice, spiritual direction offers one particular way of fostering an exciting and existentially relevant spirituality for the denomination. Through the hoped-for renewal brought about by direction, Presbyterians may well have something to say to a South Africa racked not only with violence and poverty, but also bored by an increasingly irrelevant Christianity. The essay traces that history of spiritual direction most apposite to Presbyterianism in South Africa. This includes an overview of aspects of the Celtic and African spiritual traditions with a view to finding any correspondence that would help to narrow the distance between the spirituality of its black and white members. It then asks questions about the character and tasks of directors. Highlighted is the task of fostering an awareness of God that is not purely ''heavenly minded", but is able to speak into the real issues facing Presbyterians today. The essay goes on to explore the relationship that should exist between director and directee, focussing for a moment on the direction necessary in the directee's prayer life. The essay comes full circle as it considers the implications of introducing direction more widely in this largely "directionless" denomination. As a microcosm of the country, divergent cultures are as much a reality in the P.C.S.A. as in the rest of South Africa. So respect for uniqueness and the practice of interpathy are encouraged as part of the familiarisation process. Throughout the essay, I attempt to show that spiritual direction is a means of allowing the directee to more clearly discern the voice of the Spirit, who constantly encourages the transcendence of self - viz. the breaking of and dying to old perceptions, habits and beliefs so that s/he might more fully enter into the mystery that one usually refers to as God.
Keywords: Spiritual direction; Presbyterian Church of Southern Africa